BEDA PENGARUH PEMBERIAN WILLIAM’S FLEXION EXERSICE DAN WILLIAM’S FLEXION EXERSICE DENGAN KINESIO TAPPING TERHADAP NYERI DISMENORE - Febriani, Yelva (LPPM Universitas Muhammadiyah Sumatera Barat, 2019)
Background: Dysmenorrhea or menstrual pain means uterine pain during menstruation. Dysmenorrhea is usually isolated or part of premenstrual syndrome. There are two types of dysmenorrhea, primary and secondary. The purpose of:this study was to determine the difference effects of William's Flexion exercises and William's Flexion exercises with Kinesio Tapping on dysmenorrhea pain. Methods :This research is an experimental research using the design of Two Group Pretest-Posttest Design. The sampling technique was purposive sampling with a total of 20 people divided into 2 groups, namely group-I given by William’s Flexion Exercise and group-II given by William’s Flexion Exercise with Kinesio Tapping. Each group consists of 10 people. Data collection was done by measuring dysmenorrhea pain using Visual Analogues Scale before and after intervention. Result :There were differences in dysmenorrhea pain in the I-group of 4,40 and group-II of 0,20. Different test of difference with Mann Whitney Test showed the difference between group I and group II where p value = 0.00. Conclusion : Based on the results of the study concluded that there is a Difference in the Effect of William's Flexion exercises and William's Flexion exercises with Kinesio Tapping, there william’s flexion exercise with kinesiotapping more than effective from William’s flexion exercise only. Keywords : William's Flexion Exersice, Kinesio Tapping, and Dysmenorrhea